Educational attainment does not influence brain aging - Nyberg, L; Magnussen, F; Lundquist, A; Baare, W; Bartrés- Faz, D; Bertram, L; Boraxbekk, CJ; Brandmaier, AM; Drevon, CA; Ebmeier, K; Ghisletta, P; Henson, RN; et al. (National Academy of Sciences, 2021)
Education has been related to various advantageous lifetime outcomes. Here, using longitudinal structural MRI data (4,422 observations), we tested the influential hypothesis that higher education translates into slower rates of brain aging. Cross-sectionally, education was modestly associated with regional cortical volume. However, despite marked mean atrophy in the cortex and hippocampus, education did not influence rates of change. The results were replicated across two independent samples. Our findings challenge the view that higher education slows brain aging.